The relationship between integrity and job performance among employee at Kolej Matrikulasi Pahang, Pahang Darul Makmur / Nur Fatehah Arshad - Arshard, Nur Fatehah (2019)
The existence of a sense of integrity gives a major impact on job performance. This research paper aims to study the relationship between integrity and job performance among employees. Productivity, trust, and work ethics are used as contributing variables to find out how these variables affected job performance. The study has been conducted in Kolej Matrikulasi Pahang, Malaysia where a sample of 159 employees were involved in the survey. The study has used questionnaires to collect data and from a total of 159 questionnaires sent out, only 123 respondents replied. The data then analyzed using the SPSS data analysis software. Results from the study showed productivity, trust and work ethics have a significant relationship with job performance among employees at Kolej Matrikulasi Pahang. The findings explained that employees view productivity as the most contributing variable that influence job performance and this outcome will serve to complement the employee’s role and responsibilities in achieving a high level of job performance